IMPLEMENTATION OF RELIGIOUS MODERATION VALUES AMONG STUDENTS IN PREVENTING INTOLERANCE AND RADICALISM - YENA SUMAYANA (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2023)
The purpose of this research is to provide an overview of how students are in facing global influences related to religious sentiments such as intolerance and radicalism. A narrow understanding of an event can lead to things that can undermine diversity in this country of Indonesia. This should be of more concern, especially to students who are still in the process of searching for their identity, it will be very easy for them to get mired. Therefore, a strategy is needed that can be taken by the campus in preventing students from taking actions that can harm themselves and others. Based on the research results, the condition of Sebelas April University students is in the conducive category. This is because students already understand their roles and functions as citizens. In addition, this is inseparable from the application of several approaches, both in terms of curriculum, culture, individual, system, modeling, and organization. One of the most influential approaches is the local culture approach. The results of this study are expected to be a reference in developing approaches to preventing intolerance and radicalism on campus.